Cost Structure and Function of Smoked Skipjack Fish Processing Business in North Sulawesi Province - Octalia, Vera; Sukiyono, Ketut; Romdhon, M. Mustopa (Badan Penerbitan Fakultas Pertanian (BPFP), 2025)
This research aims to analyse the cost structure of the smoked skipjack fish processing business in North Sulawesi Province, with a focus on determining the cost function and its effects. Eighty-one skipjack-smoked fish producers were censused and interviewed using questionnaires that had been prepared before. The analysis method used in this research consists of descriptive analysis and Cobb-Douglas cost function analysis, in which the cost function is modelled in the short term. The result showed that the cost of fresh fish, supplementary materials, and labour largely dominated the skipjack smoked fish processing cost. These costs account for 98.86% of the total cost; the remainder is variable costs, namely depreciation costs. From the regression analysis, the production volume and firewood price significantly affect production costs, while others do not.